1993
DOI: 10.2466/pms.1993.76.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Curricular Integration at the University of Missouri—Kansas City School of Medicine

Abstract: In its combined Baccalaureate-M.D. degree program, the University of Missouri-Kansas City School of Medicine endeavors to foster interdisciplinary integration by intertwining the humanities, clinical medicine, and basic sciences throughout the curriculum. Analysis over 6 years (1986-1991) of 547 students' scores on comprehensive examinations and ratings of 464 to 478 graduates' clinical abilities suggest that the integrative elements of the curriculum have a counterpart in performance. Such experience would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…2 Arnold and Willoughby, who examined the curricular integration at the University of Missouri and the Kansas City School of Medicine, posit that early clinical exposure will increase context as well as relevance, thereby ensuring a deeper level of learning. 3 Another study done by Wilkerson and Abelmann surveyed Harvard graduates in a health sciences program and reported that the most frequently reported reason that medical students appreciated their studies was the emphasis on integration between basic sciences and clinical (practical) medicine. 4 With respect to vertical integration of curriculum content at chiropractic colleges, Nyiendo and Haldeman reported in 1985 that, in their study based on surveys of new patients and interns at Western States Chiropractic College, there were inconsistencies with respect to interns' practice activities.…”
Section: Discussionmentioning
confidence: 99%
“…2 Arnold and Willoughby, who examined the curricular integration at the University of Missouri and the Kansas City School of Medicine, posit that early clinical exposure will increase context as well as relevance, thereby ensuring a deeper level of learning. 3 Another study done by Wilkerson and Abelmann surveyed Harvard graduates in a health sciences program and reported that the most frequently reported reason that medical students appreciated their studies was the emphasis on integration between basic sciences and clinical (practical) medicine. 4 With respect to vertical integration of curriculum content at chiropractic colleges, Nyiendo and Haldeman reported in 1985 that, in their study based on surveys of new patients and interns at Western States Chiropractic College, there were inconsistencies with respect to interns' practice activities.…”
Section: Discussionmentioning
confidence: 99%
“…Interdisciplinary education and treatment in medicine is receiving increasing attention, especially in several key areas (Strelnick et al 1988; Branch et al 1991; Burke & Inui 1992; Arnold & Willoughby 1993; Bulger 1993; Musfeldt & Hart 1993; Pearlman et al 1993; Fields et al 1995; Freeman et al 1995; Hoffman & Johnson 1995; Kahn et al 1995). For example, the development of `critical pathways' has relied upon multi‐disciplinary collaboration, and the value of this approach has been documented previously (Musfeldt & Hart 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding medical ethical issues has been facilitated by dialogue among medical ethicists, doctors from multiple disciplines, and allied health professionals (Pearlman et al 1993). Undergraduate medical education programmes increasingly emphasize interdisciplinary participation, especially as a way to foster the development of primary care (Branch et al 1991; Burke & Inui 1992; Arnold & Willoughby 1993; Fields et al 1995; Freeman et al 1995; Kahn et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the healthcare literature, the term integration is used to describe (1) the coordination of multiple disciplines in clinical care, [3][4][5] (2) the merger of mainstream and complementary medicine, 6 (3) the use of information systems to track patients or measure quality of care, (7) (4) the incorporation of women's health issues into the medical curriculum, 8,9 or (5) various financial and organizational arrangements (horizontal or vertical integration). [10][11][12] In contrast, the CoE model defines integration as a dynamic and multidisciplinary linkage of women's health practice with research, teaching, education, community outreach, and faculty development.…”
Section: Introductionmentioning
confidence: 99%